Efeito da suplementação de proteína em diferentes momentos na massa magra, adiposidade e força de mulheres na pós-menopausa praticantes de exercício contra resistência - Branco, Flávia Moure Simões de (2018)
Objective: To evaluate the effect of protein intake immediately after resistance exercise on lean mass, strength, and functional capacity gains in postmenopausal women. Methods: Thirty-four postmenopausal women (60.9 ± 6.7 years) participated in this double-blind, parallel-group, randomized clinical trial. All individuals performed the same resistance training protocol in the morning, 3 times a week, at 70% of 1-maximum repetition (1-RM) during 8 weeks. Participants were randomly assigned to protein-carbohydrate group (PC) (n=17), that ingested 30 g of whey protein immediately after exercise and 30 g of maltodextrin in the afternoon; and to carbohydrate-protein group (CP) (n=17), that ingested 30 g of maltodextrin immediately after exercise and 30 g of whey protein in the afternoon. Lean mass was assessed using dual-energy X-ray absorptiometry, handgrip strength by a dynamometer, and strength was evaluated by 1-RM of bench press and leg extension. One mile walk test was performed to assess the functional capacity. Results: Both the PC group (37.3 [35.0-39.7] to 38.1 [35.9-40.5] kg) and the CP group (38.2 [36.0-40.5] to 38.8 [36.5-41.3] kg) increased the total lean mass after the intervention (p < 0.001). An increase was also found in both groups for 1-RM bench press, 1-RM leg extension and handgrip strength (p < 0.001). In addition, the time of 1-mile walk test decreased in both groups (p = 0.019). No differences were found for group and time interaction for all variables (p > 0.05). Conclusion: The protein intake immediately after resistance exercise does not promote additional increase in lean mass, strength, and functional capacity in post-menopausal women. This trial was registered at ClinicalTrials.gov as NCT03372876.